Direct UV‐Induced Functionalization of Surface Hydroxy Groups by Thiol–Ol Chemistry1. Issue 15 (5th March 2014) - Li, Linxian; Li, Junsheng; Du, Xin; Welle, Alexander; Grunze, Michael; Trapp, Oliver; Levkin, Pavel A.
Abstract A novel UV‐initiated surface modification method for the direct functionalization of surface hydroxy groups with thiol‐containing molecules (termed "thiol–ol" modification) is described. This method is based on the oxidative conjugation of thiols to hydroxy groups. We demonstrate that different thiol‐containing molecules, such as fluorophores, thiol‐terminated poly(ethylene glycol) (PEG‐SH), and a cysteine‐containing peptide, can be attached onto the surface of porous poly(2‐hydroxyethyl methacrylate‐co‐ethylene dimethacrylate). Direct functionalization of other hydroxy‐group‐bearing surfaces, fabrication of micropatterns, and double patterning have been also demonstrated using the thiol–ol method.